Internationalization of Indonesian Eco-Print Batik: Drivers, Barriers, and Global Market Opportunities - Prayogo Kusumaryoko; Sudarmiatin Sudarmiatin; Heri Pratikto (LifeSciFi, 2026)
This study aims to systematically map and analyze the drivers, barriers, and global market opportunities in the internationalization process of Indonesian eco-print batik. This research employs a systematic literature review based on the PRISMA protocol, searching global databases from the last decade. From an initial pool of 650 articles, we ultimately selected 12 final articles for synthesis in analyzing the sustainability behavior of this creative industry. Analysis indicates that the primary drivers of internationalization are increasing global consumer awareness of green products, unique and authentic cultural motifs, and the emerging adoption of clean production technologies such as natural dyes and automated steam engines. However, the process faces significant hurdles, including low market awareness of local brands, strict compliance with international green industry standards, logistical inefficiencies, and limited digital marketing competencies among MSMEs. On the other hand, global market opportunities are expanding, particularly in Europe (such as Austria, Finland, and Norway) and the Middle East, through the use of global e-commerce platforms and effective digital branding strategies. This study concludes that the internationalization of Indonesian eco-print batik necessitates synergy between local wisdom-based product innovation and the adaptation of digital marketing strategies.